2012
DOI: 10.5424/fs/2012212-02634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of root pruning on the growth and rhizosphere soil characteristics of short-rotation closed-canopy poplar

Abstract: When poplar trees planted at a high density are canopy-closed in plantation after 4-5 years of growth, the roots of adjacent trees will inevitably intermingle together, which possibly restricts the nutrient uptake by root system. Root pruning might stimulate the emergence of fine roots and benefit the tree growth of short-rotation poplar at the stage of canopy closing. The aim of this study is to evaluate the effects of root pruning on DBH (diameter at breast height, 1.3 m), tree height, nutrients (N, P and K)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…This decrease in pH improved the solubility of phosphorus, potassium, and some salt ions [ 14 ], thereby increasing the contents of available phosphorus and potassium in the rhizosphere soil. This effect could also increase the concentration of nutrient ions in the rhizosphere soil, enhancing soil fertility and facilitating the absorption and utilization of nutrients by the root systems of poplar [ 4 , 6 ]. Previous studies on apple [ 36 ] and wheat [ 37 ] reported similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This decrease in pH improved the solubility of phosphorus, potassium, and some salt ions [ 14 ], thereby increasing the contents of available phosphorus and potassium in the rhizosphere soil. This effect could also increase the concentration of nutrient ions in the rhizosphere soil, enhancing soil fertility and facilitating the absorption and utilization of nutrients by the root systems of poplar [ 4 , 6 ]. Previous studies on apple [ 36 ] and wheat [ 37 ] reported similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the control group, light root pruning had no significant effects on the ecological environment of poplar rhizosphere soil; an effect that was significant as a result of moderate root pruning but reversed by severe root pruning. This was mainly because moderate root pruning promoted the germination of a large number of fine roots from the incision (Figs 4 – 6 ), thereby significantly enhancing root activity and producing abundant root exudates [ 4 ]. Light root pruning had a limited stimulation effect on the incision because of the large distance between the point of root pruning and the trunk; by contrast, severe root pruning severely damaged the root system because of the short distance between the point of pruning and the trunk, delaying the recovery of the root system [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations